EFFECTIVENESS OF SUBJECT ISLAMIC SHARIAH EDUCATION TO STUDENT'S INTERACTION (KEBERKESANAN MATA PELAJARAN PENDIDIKAN SYARIAH ISLAMIAH TERHADAP PERGAULAN PELAJAR) - Abdulsoma, Thoarlim; Mohd Borhanuddin, Zakaria; Dasima, Sidek (2018)
The study on the effectiveness of Islamic Shariah Education (PSI) subjects to the interaction of students in secondary schools is based on the existence of social problems in the aspects of student interaction. A study to identify these problems is due to less effective PSI learning or there are other factors that cause violations of students' moral limits in their association. Thus, the fundamental of fuqaha‟ view was used as an evidence to refer regarding the interaction in Islamic. The process of assessing the effectiveness of the PSI curriculum on student interaction in terms of understanding and appreciation only. This study used the method of questionnaire for secondary school students form five in Kuala Nerus. The results of this study found that PSI was effective in the context of restricting student interactions in their daily lives. The level of understanding of the students is high while the level of appreciation is moderate. Hence, some recommendation of improvement steps need to be taken to increase the level.